Urgensi Pembaharuan Pidana Penjara: Studi Komparatif Kitab Undang-Undang Hukum Pidana Indonesia Dan Thailand Criminal Code 1956 - Andy Yanrudy Seconegoro; Diana Lukitasari, S.H., M.H (Sebelas Maret University, 2017)
Criminal law is general prevention which has a purpose to scare someone, so it will prevent a crime to happen to the convict as well as the public. Imprisonment appears as one of prevention. Implementation of imprisonment with correctional system, are not only intended to protect the public from the dangers of crime, but also giving enlightenment to other people so they can stay away from criminal act, therefore, it is necessary to study a comparison about imprisonment in Indonesia and Thailand. This is a normative research that used statute approach and comparative study. The result is that the imprisonment in Indonesia lack of community involvement, so that prisoners who have served their criminal past was not accepted back into the community and possible will repeat their actions. In contrast to Indonesia, in Thailand, with the involvement of the community in the correctional system make the prisoners feel welcomed back into society. Keywords : comparative law, imprisonment, Indonesia, Thailand, criminal code